Atypical clinical presentations are common in TIA and minor stroke patients with DWI-MRI confirmed ischaemia. Issue 9 (12th August 2022) - Gallogly, Patrick; Best, Jonathan; Werring, David; Hassan, J; Lee, C; Cousins, J; Jäger, Rolf; Chandratheva, Arvind
Abstract : Background and Aims: Current diagnostic criteria for TIA/minor stroke disqualify several atypical clinical presentations, but pre-date DWI-MRI use. We investigated the proportion of DWI-positive patients with atypical presentations, identifying clinical factors predicting DWI positivity. Methods: We retrospectively reviewed consecutive patients with suspected TIA/minor stroke (NIHSS<5) undergoing MRI at our comprehensive stroke centre from March 2020-February 2021. We identified pre- dictors of DWI positivity using logistic regression. Results: Of 1615 patients, 442 DWI-positive, 39% had atypical presentations including 20% with progres- sive symptom onset. Atypical symptoms common in DWI-positive patients included headache(17%), unsteadiness(15%), positive sensory symptoms(11%), presyncope(10%), confusion(9%) and vertigo(8%). Symptoms independently associated with DWI-positivity included weakness(OR 1.30, 95% CI 1.01-1.67), dysarthria(OR 2.06, CI 1.56-2.70), and ataxia (OR 3.75, CI 2.27-6.20). Fluctuating symptoms(22%) predicted DWI positivity(OR 1.37, CI 1.00-1.81), but sudden onset(80%) did not (OR 1.05, CI 0.80-1.38). Risk factors associated with DWI positivity included increasing age(OR 1.01/year, CI 1.01-1.02), hypertension (OR 1.70, CI 1.30-2.22), diabetes(OR 1.44, CI 1.07-1.93), and smoking(OR 1.68, CI 1.19-2.39). DWI-positive patients had significantly more risk factors (mean 2.65 vs 1.95 p=<0.001). Conclusions: Over one-third with DWI-confirmed TIA/minor stroke present atypically. The value of atypical symptoms in excluding ischaemia, particularly in patients with vascular risk factors, appears limited.